Barriers to learning and performing in physical education in modular remote learning and coping strategies perceived by the students - Culajara, Carla Jobelle (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2022)
Every child deserves access to quality education amidst the COVID 19 pandemic. Students face the test of answering modules much more than doing the performances in the physical education classes. One of the challenges they faced was performing different performance tasks and being able to meet the objectives as well as the learning competencies. This study aimed to determine the barriers in learning performances and students’ coping strategies in physical education in modular distance learning which was accompanied by a quantitative approach using a descriptive – survey method of research. The study was conducted in one of the secondary public schools composed of 201 selected junior high school students. Based on the result of the study, the findings were as follows: majority of the of the respondents were female, grade 9 students and 15 years of age. The barriers exprienced by the students were overthinking about their grades, minimal engagement in performance tasks due to lack of equipments and learning materials, discomfort in doing the task because of distraction at home and unstable internet connection which means it is important to assess and evaluate the learning materials provided in the module to provide accessibility to students capabilities and available materials at home. With regards to students’ coping strategies, it emphasize in developing skills and abilities even in the confinement of home because learning must continue and students have the grit to do their tasks in their modules which indicates the student's opportunities and resiliency was very important factors for the students’ learning and doing performances. To satisfy the students' needs, school leaders must incorporate real methods into their teaching and address their diversity, as well as provide a variety of instructions and learning resources, lesson exemplars, and assistance for the students. To stimulate creativity and assure excellence in educational offerings, colleagues should be given technical assistance and coaching. Professional development should be prioritized during the pandemic to improve intrinsic competencies to plan, manage, and internalize more effective service delivery.